Address from Chairman of The Indonesian Association of The Faculty of Dentistry (AFDOKGI) - M Dharma Utama (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
We agree that all faculty of dentistry in Indonesia needs to contribute to dental health development. By this, hopefully we can contribute to promote oral health, prolong tooth life, and improve quality of life in our country as well as in our Asia region. To reach this goal faster, we need to exchange information and enhance scientific collaboration. The Indonesian Journal of Dental Research (The Indonesian J Dent Res) will be an effective form of communication among dentists and researchers and also a very considerable part in scientific and technological development towards the goal.Meanwhile, Indonesia is a very unique country. Although the prevalence of oral and dental diseases is considered high, but Indonesia is rich with culture, natural resources, and local or indigenous perspective which can be an advantage in term of technological perspective in dentistry. The richness of the country is needed to be investigated and explored in order to improve oral and dental health. The communication and collaboration among dentists and researchers are needed to accelerate the process towards the improvement of oral and dental health.I do hope that this journal will be an effective communication channel for better oral and dental health in Indonesia. Congratulation for the publication of the first issue of the journal. We hope to learn more from the continuous scientific communication through The Indonesian Journal of Dental Research.M. Dharma UtamaProfessor in ProsthodonticsDean of The Faculty of Dentistry Hasanuddin UniversityChairman of The Indonesian Association ofThe Faculty of Dentistry (AFDOKGI)